Challenges and Strategies of Remote Foreign Language Learning for Students with Autism Spectrum Disorder - Iryna Haidai; Liudmyla Suvorova; Nataliia Pankovyk; Yuliia Herasymchuk; Olha Zadoienko (Proceedings of the International Conference on Applied Innovations in IT)
People with cognitive impairments constantly face a number of modern challenges, including a pandemic, martial law, and instability of psychoemotional functions, which already complicates the education of students with autism. Today, inclusive education in Ukraine is only beginning to develop effectively, but global crises significantly limit full-fledged education. The difficulty lies in adaptation - a kind of «adjustment» of educational materials for people with disabilities. A gadget, which was previously perceived as a means of entertainment, a tool for obtaining pleasure or «reward», must now become an educational center, a source of knowledge accumulation. Therefore, the goal was to study how the acquired digital skills and abilities can positively affect the education of students on various distance platforms. The results of the observation showed that the advantage of students with autism is their unique ability – to be able to work perfectly with a gadget. The study offers practical and proven effective ways of teaching students with ASD. The object of study was distance learning tools tested on students of the transitional educational level – grades 4-6, who studied in an inclusive form of education. The results showed that the organization of education of students with autism in a distance format has a number of both disadvantages and advantages. Among the disadvantages: unhealthy virtual socialization; inability to adapt educational materials; blurred social roles; sensory overload; technical problems with video and connection; distraction by clips; limited opportunities for forming strategies for psycho-emotional communication. On the other hand, the studies showed that individual topics were quite effectively mastered using online platforms. These are a case-block approach to presenting material using distance technologies, game practices, and programs that help in learning a foreign language. Such a well-developed experience will become a practical find in developing inclusion at the level of professional pre-higher and higher education in Ukraine in the future.